An Innovative Approach of Multi-Focus Image Fusion Using SWT and Content Adaptive Blurring - Sahoo, Tapasmini; Acharya, Richa; Kaumar Das, Kunal (International Journal of Engineering and Technology, 2018)
This paper depicts a stationary wavelet transformation based image fusion technique in association with content adaptive blurring.Â  The fusion technique combines multiple images of the same scene with different resolution, intensity to get a combined image with more suitability for extracting features which is difficult to find from an image in various modalities. The performance and relative importance of the proposed fusion technique is investigated by some statistical evaluation measures. The values of the statistical measure suggests that the execution of the proposed strategy is appreciable. It likewise improves the visual impact.Â